Biomass Carbon Sequestration Potential of Conifers in Relation to Tree Structural Traits and Anthropogenic Disturbance Stimuli in Kashmir Himalaya - Khan, Raja Waqar Ahmed; Shaheen, Hamayun; Dar, Muhammad Ejaz Ul Islam; Awan, Shahzad Naseer; Qayyum, Seema; Nazir, Nimra; Ahmed, Khawaja Waqas; Awan, Muhammad Shakeel (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
It is essential to quantify the amount of carbon stored in the biomass of forest species to determine the potential for mitigating climate change through forest management. This study aimed to estimate the biomass carbon stock (BCS) of coniferous tree species in 16 temperate (TFs) and 4 subalpine forests (SFs) in the state of Azad Jammu and Kashmir (AJK). BCS was calculated for individual trees using allometric equations. The total BCS was 66.5 ± 6 .8 Mg ha-1, with 42.4 ± 7.3 Mg ha-1 (63.7%) in TFs and 24.2 ± 4.1 Mg ha-1 (36.3%) in SFs. The dominant species, Pinus wallichiana A.B. Jacks. and Picea smithiana (Wall.) Boiss., had corresponding BCS totals of 22.4 ± 4.6 (33.7%) and 21.7 ± 4.8 Mg ha-1 (21.7%), respectively. Abies pindrow Royle had a BCS of 14.1 ± 3.8 Mg ha-1 (21.2%), while the lowest value of 8.3 ± 1.3 Mg ha-1 (15.5%) was found in Cedrus deodara (Roxb. ex D. Don) G. Don. TFs showed healthier structural attributes, with higher tree diameter at breast height (DBH) (155.7 ± 8.2 cm) and density (157.1 ± 4.2 trees ha-1) compared to SFs, which had lower DBH (131 ± 7.4 cm) and density (113.9 ± 7.7 trees ha-1). The forests in this region are facing significant deforestation, with 154.0 ± 6.4 stumps ha-1 in temperate forests and 48.8 ± 2.8 stumps ha-1 in subalpine forests. Statistical analysis revealed a significant correlation between BCS and tree girth, height, and total stem density. This study highlights the allocation trends of BCS among keystone species in a climate-sensitive region and emphasizes the need for forest conservation in the context of climate change.